2015
DOI: 10.1002/rnj.211
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fall Risk Assessment Specific to the Inpatient Rehabilitation Facility Setting

Abstract: Purpose: To evaluate and compare the Morse Fall Scale (MFS) and the Casa Colina Fall Risk Assessment Scale (CCFRA) for identification of patients at risk for falling in an acute inpatient rehabilitation facility. The primary objective of this study was to perform a retrospective validation study of the CCFRAS, specifically for use in the inpatient rehabilitation facility (IRF) setting. Design: Retrospective validation study. Method: The study was approved under expedited review by the local Institutional Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Fall assessment tools, which are commonly used to predict which patients are likely to fall or not, are designed for use in specific healthcare settings1–18 for a specific disease,7 13 19–22 for patients of a similar age3–6 10 14 16 20 23–25 or for general use 26–28. Previous reports compare the predictive values of one tool with another8 9 15 17 20 26 or evaluate the predictive value of a single tool,6 7 14 29 30 then fault the tool's predictive ability when it appears that the tool grossly overestimated or underestimated the likelihood of fall. Predictive ability is further confounded because risk is not recalculated and adjusted after implementation of fall prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Fall assessment tools, which are commonly used to predict which patients are likely to fall or not, are designed for use in specific healthcare settings1–18 for a specific disease,7 13 19–22 for patients of a similar age3–6 10 14 16 20 23–25 or for general use 26–28. Previous reports compare the predictive values of one tool with another8 9 15 17 20 26 or evaluate the predictive value of a single tool,6 7 14 29 30 then fault the tool's predictive ability when it appears that the tool grossly overestimated or underestimated the likelihood of fall. Predictive ability is further confounded because risk is not recalculated and adjusted after implementation of fall prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these assessments were previously found to poorly predict fall risk in rehabilitation settings [29,31,32]. As well, some SCI rehabilitation hospitals in the current study used customized fall risk assessments, but some of these tools lack psychometric standardization [14]. Further, it has been suggested that the use of risk assessment scores to determine fall risk in rehabilitation is an ineffective use of staff time due to the lack of useful information produced [31].…”
Section: Discussionmentioning
confidence: 84%
“…For instance, all sites used different risk assessments. The purpose of a risk assessment tool is to assist clinicians in identifying sub-groups of individual patients at high risk of falling [14]. Fall risk assessment is a required practice for healthcare organizations to achieve accreditation [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of FRSTs have been developed in different patient settings, but few have been developed specifically for inpatient rehabilitation (Sherrington et al., ; Thomas, Pavic, Bisaccia, & Grotts, ). Consequently, FRSTs developed in acute care settings are often used in rehabilitation (Lee, Geller, & Strasser, ).…”
Section: Introductionmentioning
confidence: 99%